CLASSIFICATION OF CRIMES AND VIOLATIONS IN THE IMMIGRATION ACT - Maidah Purwanti (Jurnal Ilmiah Kajian Keimigrasian, 2018)
The mention of 'violations' in any criminal act that violates the criminal provisions of the Immigration Law, certainly cannot be allowed to go on, because the theory of criminal law has classified the distinction between Crime and Violation. Likewise, in the formulation of the Immigration Law Criminal Provisions, there has been a fairly clear distinction between crime and violation itself. Through a theoretical study of punishment, this short and simple writing provides a description of the location of the distinction, which is very easy to identify. The condition needed is re-habituation to differentiate the mention of immigration crime in accordance with its classification.